Holistic Care as one of Healing Garden Therapy Program (HGTP) Implementation In Hospital A Qualitative Study - Hastuti, Agustina Sri Oktri; Lorica, J D; Effendy, Christantie (Jurnal Keperawatan Respati Yogyakarta, 2025)
The Healing Garden Therapy (PGHT) program is intended to improve the physical, mental, social, and spiritual health conditions of patients, visitors, and staff at the Hospital. In this activity, in addition to being participants, health workers also play a role in organizing PGHT. This study contributes to health workers, especially nurses, to implement holistic services for patients. This study is an exploratory qualitative study to explore the perceptions of health workers in the implementation of PGHT. The sample of this study was 13 health workers who had been involved in the implementation of the PGHT at Panti Rapih Hospital Yogyakarta and St Carolus Jakarta, which were taken using purposive sampling techniques. The researcher conducted in-depth interviews with participants, with the help of a recording device and interview guidelines that had been prepared previously. The reporting of the research results has been based on the COREQ Checklist. The results obtained themes; The Healing Garden Therapy program in hospitals is educational and innovative; Has challenges, and opportunities and requires commitment from all components of the hospital in further program development; The Healing Garden Program in hospitals is a manifestation of holistic nursing; The Healing Garden Program in hospitals is very beneficial for patients, families/visitors and hospital employees; and A garden design is needed that supports the implementation of the Healing Garden Program in hospitals. The implementation of the Healing Garden Program is beneficial for patients, visitors, and health workers, so efforts need to be made to be implemented in every hospital.